Challenges and measures during management of mounting biomedical waste in COVID-19 pandemic: an Indian approach - Manekar, Snehal S. (2023)
The length of one's life is related to the amount of garbage produced. Waste is generated by a variety of activities such as households, industrial, agricultural, institutional, municipal, commercial, and so on (Vergara and Tchobanoglous 2012). In industrialized areas, the amount of waste generated is high, but the awareness about waste management is lacking (Ferronato and Torretta 2019).